Projecting Tourism Development of Rural Area Based on Customer Satisfaction: SWOT Analysis Study - Solihin, Riadatus; Demolingo, Ramang H.; Pattaray, Anas; Bahtiar, M. Rifqi Subakti (CV ODIS, 2024)
This paper aims to analyze and assess the strengths and weaknesses of Tete Batu tourism village to recommend its development strategy. It is a qualitative case study, and the sample of this study was four tourism actors and 25 visitors selected through the snowball sampling technique. The interview was the instrument used to collect the data. The data were analyzed through some steps: transcription, categorization, data coding, and data interpretation. The result shows four strengths of Tete Batu tourism village: diversity of destinations, amenities, tourism activities, and government sports. Secondly, accessibility, human resources, and ancillary services are the weaknesses of Tete Batu tourism village. Finally, there are several activities that Tete Batu can implement: extending the market share by targeting domestic customers, developing the four main attractiveness of the village based on customer preferences (destinations, amenities, tourism activities, and friendly local hospitality), developing sports tourism, cooperating with the government to provide some training and build up facilities, and applying an alliance management strategy with competitors.